2017
DOI: 10.1016/j.microc.2017.03.048
|View full text |Cite
|
Sign up to set email alerts
|

High throughput determination of ammonium and primary amine compounds in environmental and food samples

Abstract: In this paper, an improved spectrofluorimetric method for the simultaneous and direct determination of ammonium and primary amine compounds is presented. The method is based on the derivatization with o-phthaldialdehyde (OPA) / N-acetylcysteine (NAC) reagent using high throughput microplates, and OPA/NAC ratio has been optimized in order to suppress interference of ammonium on primary amine determination. Direct measurement of these two parameters is therefore possible with a global procedure time that does no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…The preservation of OPA/NAC reagent has already been studied previously [ 35 ]. It had been shown that OPA and NAC solutions were stable for up to four months, provided these solutions were stored separately at 4 °C in the dark.…”
Section: Resultsmentioning
confidence: 99%
“…The preservation of OPA/NAC reagent has already been studied previously [ 35 ]. It had been shown that OPA and NAC solutions were stable for up to four months, provided these solutions were stored separately at 4 °C in the dark.…”
Section: Resultsmentioning
confidence: 99%
“…NH 4 + analysis was carried out by microplate assays following a protocol described in a previous paper based on NH 4 + derivatization with o -phthaldialdehyde (OPA)/ N -acetylcysteine (NAC) . The method LQ was17.07 μg L –1 .…”
Section: Methodsmentioning
confidence: 99%
“…The main goal of our work was to develop a new sensitive method for the determination of nitrate by a microplate-based procedure in compost aqueous extracts. In the past, our research group has developed various analytical methods based on the 96-wells technique [17][18][19][20]. In particular, a fluorescence-based microplate procedure for the quantification of ammonium and primary amines in compost water extracts and other matrices was recently assessed [17].…”
Section: Monitoring Of Nitrate In Various Environmental Samples In Thmentioning
confidence: 99%
“…In the past, our research group has developed various analytical methods based on the 96-wells technique [17][18][19][20]. In particular, a fluorescence-based microplate procedure for the quantification of ammonium and primary amines in compost water extracts and other matrices was recently assessed [17]. The basic idea for the assessment of our method was to exploit the previous protocol, reducing first the nitrate to ammonium and then quantifying the latter by means of the method already assessed.…”
Section: Monitoring Of Nitrate In Various Environmental Samples In Thmentioning
confidence: 99%